2017
DOI: 10.1016/j.foodhyd.2017.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimisation of octinyl succinic anhydride starch stablised w 1 /o/w 2 emulsions for oral destablisation of encapsulated salt and enhanced saltiness

Abstract: Sodium (salt) was encapsulated within the inner water phase of w1/o/w2 food emulsions externally stabilised by starch particles with the ultimate aim of enhancing saltiness perception. The physical properties of the starch particles were modified by octenyl succinic anhydride (OSA) treatment (0–3%) to vary the degree of hydrophobicity of the emulsifying starch. During oral processing native salivary amylase hydrolysed the starch and destabilised the o/w emulsion releasing the inner w/o phase and subsequently s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 21 publications
0
25
0
Order By: Relevance
“…Finally, the design and outcomes of a brief study applying a WRS stabilised wow emulsion to salt reduction in a tomato soup are reported in the Appendix, validating this salt reduction approach not only for a model food, i.e. an emulsion, 11,12 but for a real food.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Finally, the design and outcomes of a brief study applying a WRS stabilised wow emulsion to salt reduction in a tomato soup are reported in the Appendix, validating this salt reduction approach not only for a model food, i.e. an emulsion, 11,12 but for a real food.…”
Section: Introductionmentioning
confidence: 82%
“…The obvious choice of an emulsifier was a starchbased emulsifier, hydrolysing in contact with the salivary amylase. In the cited literature, chemically modified octinyl succinic anhydride (OSA) starch was used, which was later optimised, 12 and all sensory testing to draw conclusions about showing potential to allow a plus 20% reduction of salt in emulsion-based foods was based on assessing emulsions alone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also applied for emulsion stabilisation have been OSA modified native starch granules ( Timgren, Rayner, Sjöö & Dejmek, 2011 ; Rayner, Timgren, Sjoo & Dejmek, 2012 ). Preparing our own gelatinised OSA modified waxy maize starch with a degree of modification between 0% and 3%, corresponding to the upper level allowed for OSA modified starch as a food ingredient, we were able to demonstrate that the degree of OSA modification was negatively correlated to tastant perception ( Chiu, Tarrega, Parmenter, Hewson, Wolf & Fisk, 2017 ). However, at less than 2% OSA modification the microstructure of the emulsions was stable only for up to a few days, rendering this approach to reduce salt or sugar in emulsion-based foods commercially almost irrelevant.…”
Section: Introductionmentioning
confidence: 98%
“…Octenylsuccinated starch (OS‐starch) shows wide application in the food industry, mainly as emulsifier or Pickering emulsion and encapsulating agent . However, information on the octenylsuccinylation of oxidized starch as a surface sizing agent in papermaking is limited.…”
Section: Introductionmentioning
confidence: 99%